Determination the Biggest Factor Criteria in A Decision Support System with Analytical Hierarchy Process (AHP) Methods Using Iterative Dichotomiser 3 (ID3) Algorithm - Riki Andrian, Aristoteles Machudor Yusman Tubagus (SEMIRATA 2015, 2015)
Each company periodically conducts recruitment. With the decision support system is expected to help the company in recruitment. There are various methods to build a DSS and one of them is AHP methods. AHP is one method that can handle the selection of DSS multi-criteria. In each selection, raises the question whether the most influential criteria in the same selection. Using the results from the DSS with AHP methods as sample data, the ID3 algorithm is used to find the biggest factor in the screening criteria. These results indicate the criteria are favored in the weighting criteria are not always the biggest factor and the biggest criteria factors tend to have a wider range of data than other criteria. Keywords: Analytical Hierarchy Process (AHP), Iterative Dichotomiser 3 (ID3), Decision Support Systems (DSS).